OPTIMAL CABLE SELECTION IN RADIAL DISTRIBUTION NETWORKS CONSIDERING PLANNER'S DEFINED VOLTAGE DROP LIMIT - Ab Ghani, Mohd Ruddin (2002)
New computer algorithms are provided to determine the optimal cable size selection considering radial distribution networks and planner of power distribution defined allowable voltage drop all over the networks. The planner should properly populate the location of all load substations and joint node location in the input data source. Distance calculation of the demand node to demand node and joint node to joint node etc. depends on the geo-graphical location of the defined node. Cable size and type of all feeder segment determination depends on the total cost of the networks, cost of feeder losses etc. An acceptable voltage profile will be maintained all point of the entire networks. The resource of the cable inventory is also responsible for optimal selection of the cable. By using this proposed computer algorithm and program an example is solved successfully that is presented in the results.